Professional language – specialized language: language variant, sociolect, style or pragmalect? A critique of the (pre)term pragmalect in the context of multiple methodological approaches - Jarosz-Mazur, Beata (Papers in Linguistics, 2026)
The article concerns the functionality of describing professional and specialised languages with the use of pragmalect, a recently coined term, instead of the previously applied term sociolect, generally understood as a variant of language used in specific social groups, but also associated in functional pragmatics with all variants of language. The word pragmalect has a clear structure and can intuitively be linked to language/speech (-lect) that is used to achieve a specific communicative goal (Gr. prágma ‘action’). A substitution experiment involving the replacement of the terms sociolect and language variant with the preliminary term (pre-term) pragmalect in excerpts from Polish academic texts on professional and specialized languages has revealed significant complications that can arise because of the postulated implementation of this word. These problems are caused both by the multiplicity of methodological approaches (including the nonidentity of języki zawodowe [professional languages] and języki specjalistyczne [specialized languages/languages for specific purposes], recognizing them or not as language variants, sociolects or styles), and by the necessity of applying the typology of pragmalects (associated with the pre-term), within which it is difficult to adequately place professional subcodes.